Kajian Kebijakan Keamanan Sistem Informasi Sebagai Bentuk Perlindungan Kerahasiaan Pribadi Karyawan Perusahaan BFI Finance - Hafizd, Daffa Al; Asnawi, Azi; Assidiqie, Muhammad Fikri (Jurnal Sains dan Teknologi (JSIT), 2023)
Technology that connects computers around the world makes it possible to exchange information and data and even communicate with each other in the form of images and videos. The more valuable information is, the more security standards are needed to protect that information. The goal of computer security, among others, is to protect information. The higher the security standards provided, the higher the privacy protection of information. Protection of employee privacy in a company is one of the factors that must be considered in the implementation of information systems. Information system security policies include: System maintenance, risk management, setting access rights and human resources, security and control of information assets and server security policies. The policies that have been reviewed will not only be a form of protection for company information, but also a form of protection for the personal privacy of employees of BFI Finance Company..